2017
DOI: 10.1111/aej.12212
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary techniques for pain control during root canal treatment of lower posterior teeth with irreversible pulpitis: A systematic review and meta‐analysis

Abstract: The purpose of this systematic review and meta-analysis was to evaluate utilisation of supplementary techniques for pain control during root canal treatment of lower molars with irreversible pulpitis. The literature was searched using electronic databases up to year 2012. Seventeen studies with 1504 participants were included and each study compared experimental interventions with a standard treatment, i.e. the inferior alveolar nerve block. Changing the injection techniques or supplemental injection had no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 17 publications
0
26
0
6
Order By: Relevance
“…, Tupyota et al . ). NSAIDs affect the production of prostaglandins (PGs) and thromboxane A2 responsible for mediating inflammation by reversibly inhibiting cyclooxygenase pathway.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…, Tupyota et al . ). NSAIDs affect the production of prostaglandins (PGs) and thromboxane A2 responsible for mediating inflammation by reversibly inhibiting cyclooxygenase pathway.…”
Section: Discussionmentioning
confidence: 97%
“…, Tupyota et al . ) reported that oral premedication with NSAIDs increased the success rate of IANB in teeth with irreversible pulpitis. However, the effect of various premedication drugs could not be compared to each other as they were not studied in head‐to‐head trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Tupyota et al . ) have been published on the topic related to anaesthetic success of inferior alveolar nerve block. Controversially, local anaesthesia studies did not achieve sufficient citations to be included in the list of the top most‐cited 100.…”
Section: Discussionmentioning
confidence: 99%